STUDIES OF REACTION MECHANISM AND PHYSICAL NATURE OF LIGHT-WEIGHT BASIC MAGNESIUM CARBONATE (Biological Sciences - PJSIR, 2004)
The reaction mechanism of light - weight magnesium carbonate has been studied and concluded that it is based upon formation of colloidal magnesium hydroxide and adsorption of HCO3 ions on magnesium hydroxide surface under optimum conditions. Precipitation, carried out in the presence of sodium bicarbonate over a concentration range of 1M to 0.01M, is a continuous function of the carbon dioxide remaining in the solution. Temperature between 70°C and 80°C, stirring speed of 900 rpm, gradual addition of magnesium sulfate solution and mass ratio of soda ash to sodium bicarbonate (3:2) were found to be the optimum conditions for obtaining light - weight magnesium carbonate.